The Effectiveness of hrGFP Gene Reporter Role in Carp Fish (Cyprinus carpio) Transgenesis Process Based on Convocal Microscopy Analysis - Anitasari, Septi; Soeprijanto, Agus; Faqih, Abd. Rahem (Graduate School, Universitas Brawijaya, 2015)
Sperm cells can be used as a medium to insert foreign DNA into the egg. Electroporation humanized renilla reformis Green Fluorescent Protein (hrGFP) gene as a reporter gene is very important to know the effectiveness of gene transfer. Research is aimed to understand the effectiveness rate of hrGFP gene reporter to detect the successful gene transfer process based on the result of observation with convocal microscope over transgenic sperm level, embryo and larva of Carp Fish. Result of trans-genesis of hrGFP as sperm-mediated gene reporter must be accurately detected. Based on the result of observation with convocal microscope, it is shown that hrGFP enters the core level, indicates by PI pigmentation and thereby, hrGFP gene reporter can provide information about hrGFP fluorescence starting from sperm, embryo and larva of Carp Fish.Keywords: Carp Fish, effectiveness, gene reporter, hrGFP, sperm fluorescence.